Privatization and coercion: The question of legitimacy - Fitzgibbon, Wendy (Theoretical criminology, 2018)
This article explores issues surrounding the legitimacy of private sector provision in criminal justice. It examines changes in ideas about legitimate coercion which have made private sector involvement possible. It then elaborates two models of the processes whereby private sector entities attempt to obtain and maintain the legitimacy of their activities in the eyes of the public.